2005
DOI: 10.1111/j.1439-0418.2005.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Study on some bioecological aspects of Eldana saccharina Walker (Lep., Pyralidae) on Zea mays L. and alternative host plants

Abstract: In an attempt to set up habitat management strategy against Eldana saccharina Walker, an economically important graminaceous stem and cob borer, two laboratory experiments were carried out. The first experiment was designed to assess oviposition preference of E. saccharina for growth stages, plant parts and freshness of different host plants and between host plants species. Zea mays L., Sorghum arundinaceum (Desv.) Stapf, Andropogon gayanus Kunth, Panicum maximum Jacq., Pennisetum polystachion (Linn.) and Cype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…These results for what is now known to be a southern African biotype of E. saccharina (Assefa et al. 2006) are in agreement with the findings of Atachi et al. (2005), who showed in the West African biotype that post‐tasseling stage non‐ Bt plants were more attractive than plants in the pre‐tasseling or tasseling stages of development.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results for what is now known to be a southern African biotype of E. saccharina (Assefa et al. 2006) are in agreement with the findings of Atachi et al. (2005), who showed in the West African biotype that post‐tasseling stage non‐ Bt plants were more attractive than plants in the pre‐tasseling or tasseling stages of development.…”
Section: Discussionsupporting
confidence: 91%
“…The results of several studies have now shown that E. saccharina oviposits preferentially on dry leaf material, not only in sugarcane (Atkinson 1980; Leslie 1990; Mabulu and Keeping 1999) and maize (this study; Atachi et al. 2005), but also in sedges Cyperus dives C.B.Cl., C. latifolius Poir (Atkinson 1980) C. papyrus L. (Atachi et al. 2005) and grasses Sorghum arundinaceum (Desv.)…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the same study, oviposition preference and immature performance were greater on johnsongrass than on vaseygrass. Eldana saccharina shows oviposition preference for wild graminoid hosts as compared to corn (Atachi et al., ; Conlong et al., ). However, performance is inversely associated with preference on these hosts, with longer immature development, lower survival, and lower pupal weight observed on wild grasses than on corn (Shanower et al., ; Atachi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…1985; Mazodze and Conlong 2002) and the different populations of E. saccharina feeding on different species of host plants in various parts of Africa (Conlong 2001; Matama‐Kauma et al. 2002; Atachi et al. 2005).…”
Section: Introductionmentioning
confidence: 99%